Digital nomadism an opportunity for low-density territories: Trás-os-Montes lands case - Garcez, Ana (2022)
Digital nomadism is a relatively recent tourism segment associated with the generalization of information and communication technologies (ICTs), having increased notoriety and relevance with the COVID-19 pandemic. This public is characterized by professionals who exclusively work online, while having an independent lifestyle, balancing work and leisure. This research aims to understand if the Trás- os-Montes Lands (a small region in the northeast of Portugal) hold the necessary conditions to position itself as an attractive destination for digital nomads. To this end, a macro analysis of the characteristics of this territory and the tourist accommodation in the region was carried out. In view of the results obtained it was found that although Trás-os-Montes Lands have touristic potential ability to meet the particular needs of the digital nomads segment, it is necessary an action plan to enhance the attractiveness of the destination for this audience.